Economic Evaluation of Pasture Management Systems in Arid Areas of Western Rajasthan - Kalla, Jagdeesh C; Bhati, G N (Annals of Arid Zone, 2016)
The economic analysis of three alternative pasture production systems viz., natural protected, natural protected with soil conservation measure) and the sown pasture with improved technology and soil conservation measures, was carried out in relation to grazing (sheep, cattle and mixed). fodder marketing and seed-fodder marketing options. All the options were economically viable under the identified production technologies. However. the improved technology for pasture production systems was found to be less cost-effective. To generate viable returns in the long-run, such cultivated pastures haveto be near the fodder demand points.